The Beginning of Hungarian Statehood and the Image of the Árpáds and their People - Kanas, Rafał; Grancow, Patryk; Gorzkiewicz, Bartłomiej; Chyliński, Piotr; Kołata, Zuzanna; Jastrząbek, Jakub; Agnieszka Gralak (Vade Nobiscum, tom XXV/2025: Varia, 2025)
In this article, I address the beginnings of Hungarian statehood as presented in Historia Salonitana, as well as the accompanying portrayal of the Hungarians and their rulers. My aim is to demonstrate that the opinion suggesting Thomas harbored animosity towards the Magyars needs significant nuance. To achieve this, I will primarily utilize classical methods of historical research. I will cover topics such as the arrival of the Hungarians in Pannonia, their Christianization during the reign of Prince Géza, and the rule of the first Hungarian king, Stephen I.